2022
DOI: 10.1371/journal.pone.0269280
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cannabis use and taurine: A MRS and metabolomics study

Abstract: Taurine is an essential amino acid. It has been shown to be neuroprotective including protecting against the neurotoxic effects of glutamate. The goal of the current study was to examine the relationship between CB use and taurine measured in brain using magnetic resonance spectroscopy (MRS), and peripherally from a urine sample. Two experiments are presented. The first is a reanalysis of published data that examined taurine and glutamate in the dorsal anterior cingulate of a CB user group and non-user group u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Metabolic profiling of taurine has also been extended to other neural derived tumors such as medulloblastoma, neuroblastoma, and retinoblastoma ( Kohe et al, 2018 ). Recently, a brain MRS study in cannabinoid users, found that taurine concentration was directly correlated with glutamate, and with the frequency of cannabinoid use ( Newman et al, 2022 ). Furthermore, MRS measurements determined elevated concentrations of taurine in the cerebellar vermis of bipolar patients ( Magnotta et al, 2022 ), and levels of taurine were significantly related to the duration of illness in schizophrenic patients ( Shirayama et al, 2010 ).…”
Section: Taurine As a Therapeutic Alternative In Nervous System Patho...mentioning
confidence: 99%
“…Metabolic profiling of taurine has also been extended to other neural derived tumors such as medulloblastoma, neuroblastoma, and retinoblastoma ( Kohe et al, 2018 ). Recently, a brain MRS study in cannabinoid users, found that taurine concentration was directly correlated with glutamate, and with the frequency of cannabinoid use ( Newman et al, 2022 ). Furthermore, MRS measurements determined elevated concentrations of taurine in the cerebellar vermis of bipolar patients ( Magnotta et al, 2022 ), and levels of taurine were significantly related to the duration of illness in schizophrenic patients ( Shirayama et al, 2010 ).…”
Section: Taurine As a Therapeutic Alternative In Nervous System Patho...mentioning
confidence: 99%